(untitled) - 1859-1924.; Herbert, Victor; d. 1924.; MacDonough, Glen; 1892-1957.; 1887-1956.; Rogers, Charles; 1893-1940.; Meins, Gus; 1892-1992.; Roach, Hal; Hardy, Oliver (Santa Monica, CA, 2006)
Laurel and Hardy star as clumsy toy makers who must stop the evil Barnaby and his plot to marry Little Bo Peep.
Keywords: Characters; Mother Goose; Toymakers; Drama; Toys; Drama; Fantasy films; Comedy films; Feature films; Feature; Fantasy; Feature; Comedy; Films for the hearing impaired